Study on permeability characteristics of dense-graded asphalt concrete based on the meso-structure - Sheng, Ruiqi; Liu, Wenzheng; Wei, Haobo; Huang, Xudong; Zhang, Heng; Lin, Zihe; Sun, Bowei; Liu, Jiayao (Frontiers in Built Environment, 2025)
Water damage caused by rainwater permeation significantly affect the durability of asphalt pavements. However, previous research lacked investigation of the permeability of dense-graded asphalt concrete (DGAC) from the view of meso-structure. This study systematically investigates the effects of nominal maximum aggregate size (NMAS) and compaction effort on the meso-scale pore structure of DGAC, further quantitatively analyzing the correlation between pore characteristics and permeability. In addition, an innovative “transparent dense-graded asphalt concrete” (TDGAC) method is applied to realize the visualization of the permeation process is asphalt mixtures. The results show that increasing compaction effort significantly reduces total air void contents and maintains the longitudinal “bathtub-shaped” distribution pattern. Besides, larger NMAS leads to more interconnected medium-large pores and a larger equivalent diameter of voids, which in turn results in higher permeability. Additionally, 5% and 7% air void contents are identified as critical permeability thresholds for AC-13 and AC-20, respectively. The correlation analysis indicates that permeability is primarily controlled by the pores with a volume larger than 5 mm3. The TDGAC visualization results directly confirm that the interfaces of coarse aggregates are the main pathways for water migration. The study explains the influence of compacting factors on meso-structures of DGAC, and establishes the relationship between pore characteristics and permeability, providing a theoretical basis to understand the mechanism of water-related pavement distress.